2021
DOI: 10.1155/2021/6636130
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Contributing to the Motorcycle Crash Severity in Pakistan

Abstract: Motorcycle is a popular mode of transportation in many developing countries, including Pakistan. Since the last decade, the registered number of motorcycles in Pakistan has increased by six times, constituting 74% of the total registered vehicles. However, limited research efforts have been made to investigate motorcycle-related safety issues in Pakistan. Thus, the relationship between potential risk factors and injury outcomes of motorcycle crashes is still unclear in the country. This study, therefore, estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 52 publications
3
20
0
Order By: Relevance
“…In this regard, Pervez reported that heavy vehicle is positively associated with fatalities. He found that motorcycles with heavy engines have greater performance that gives less reaction time to the riders in the event of a collision; thus, it increases the likelihood of fatality or injuries (35). According to our results, daily use of motorcycles increased the likelihood of high-risk behaviors, which was consistent with the study by Heydari.…”
Section: Discussionsupporting
confidence: 92%
“…In this regard, Pervez reported that heavy vehicle is positively associated with fatalities. He found that motorcycles with heavy engines have greater performance that gives less reaction time to the riders in the event of a collision; thus, it increases the likelihood of fatality or injuries (35). According to our results, daily use of motorcycles increased the likelihood of high-risk behaviors, which was consistent with the study by Heydari.…”
Section: Discussionsupporting
confidence: 92%
“…The findings of this study are similar to India wherein an observed trend in increasing road traffic accidents from 2005 to 2015 was attributed to increasing vehicles on the Highly significant association road. 7 Moreover, studies have also associated road accidents with sociodemographic characteristics (mean age of 32.3 ± 18.5 years, males, single), helmet use, time of the day (fatal accidents at midnights), and behaviors, [8][9][10][11][12] which were the main variables in this study.…”
Section: Discussionmentioning
confidence: 80%
“…This finding is similar to the study done in Rwanda wherein majority of victims were aged 20 to 45 years, and in New Delhi wherein 47.4% of road traffic injury patients were aged 16 to 30 years. 13,14 This may be attributed to the fact that younger people are more at risk for engaging in risky behaviors such as speeding, drifting, one-wheeling competitions, rash driving, reckless and aggressive driving, impulsivity, and drunk driving, 11 while older adults are more experienced and cautious. 15,16 The study showed that males (72.5%) were more likely to be involved in road crash compared to females (27.5%).…”
Section: Discussionmentioning
confidence: 99%
“…where S in is the utility function, β i denotes the vector of estimable parameters, X in is a vector of the explanatory variables, and ε in is an error term [29]. is study developed a random parameter logit model to overcome the limitation of multinomial logit model, that is, the influence of variables on the crossing behavior is fixed among riders, as shown in the following formula [30]:…”
Section: Analysis Methodmentioning
confidence: 99%